RATIONAL CHOICE OF PARAMETERS FLUSH THE ULTRAFILTRATION MEMBRANE - , С. М., А. С., Д. А. (Municipal economy of cities. Series: «Economy science», 2013)
The washing of plant membranes with a "dead-end" filtration are considered. The justification of washing parameters which minimize time washing and the amount of washing water are presented.